Potensi Tepezza (Teprotumumab) dalam Pengobatan Penyakit Mata Tiroid Aktif (TED) - Rukmana, Dewi Samudra Putri Aliffa; Ramzi, Rani Nurmala; Dhuarte, Jevon; Jaya, Fitra; Anugrahsari, Santi (Universitas Kristen Krida Wacana, 2024)
Abstract Active Thyroid Eye Disease (TED) is a medical condition involving swelling of the muscles, tissues, and fats around the eyes. This can lead to serious symptoms including double vision and vision loss. Tepezza (Teprotumumab) is an innovative therapy that inhibits the insulin-like growth factor 1 receptor (IGF-1R) and has been approved for TED treatment. Teprotumumab works by reducing inflammation and TED symptoms. Pharmacokinetic studies indicate that this drug can be effectively administered via intravenous infusion. Various studies have shown that teprotumumab can significantly reduce proptosis, diplopia, and clinical activity of TED. This therapy has proven effective in various patient groups, including those with long-standing TED and those unresponsive to other treatments. Teprotumumab holds a promising breakthrough in TED management, improving the quality of life for individuals affected by this disease. Further studies are needed to fully understand the mechanism and potential of teprotumumab in TED treatment.